Simulasi 3 Skenario Perbaikan Kemacetan Jagir Wonokromo Dampak dan Implementasi - Novaldo, Adrianus; Gunawan, Ivan; Rahma, Charisma; Dwi, Ryan; Tri, Feliana; Dwi, Yanuar; Pradana, Johan Alfian (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2024)
Traffic congestion in Indonesian cities is a major problem, due to uneven mobility. The Jagir Wonokromo intersection, one of the busiest intersections in Surabaya, experiences traffic congestion during rush hour. This congestion can have a variety of negative impacts, such as air pollution and queuesat each intersection. This study analyzes the traffic congestion problems at the Jagir Wonokromo intersection and proposes the appropriate improvement scenario. A simulation design was developed to test three traffic congestion improvement scenarios at the Jagir Wonokromo intersection in Surabaya. The study sample was 40 vehicles that passed through during rush hour. The simulation results showed that scenario 3 is the most appropriate improvement scenario. This scenario successfully reduced the time in the system by 20.2% compared to the initial condition. The impact of scenario 3 is that traffic congestion at the intersection is reduced, but the travel time of vehicles from the DTC direction to Jalan Jagir Wonokromo also increases. Scenario 3 is considered to be in accordance with the conditions of the intersection and can be easily implemented. The study of traffic congestion at the Jagir Wonokromo intersection offers opportunities for the government and the public to address traffic congestion with effective simulation of improvement scenarios.